Lung-Digit Syndrome Related to an Adenosquamous Feline Lung Carcinoma - de Paiva, Felipe Noleto; Ferreira de Andrade, Max; Caicó Collares Araújo, Dayane; da Silva Goes, Rafaela; Souza Costa, Thiago; Nogueira Carvalho, Vivian de Assunção; Israel Fernandes, Julio (Acta Scientiae Veterinariae, 2020)
Background: The lung-digit syndrome is a rare syndrome characterized by the presence of a primary pulmonar neoplasia manifesting metastasis to the digit, occurring exclusively in felines. The diagnosis is based on the clinical signs, associated with radiographic and histopathological exams. There are no therapeutic protocols well-established, and surgical excision is considered controversial due to high recurrence and metastasis rates. The prognosis is considered poor, with low survival rates. The aim of this paper is to report a case of lung-digit syndrome attended in Rio de Janeiro. Case: A 12-year-old female cat, no defined race, was attend with the complaint of weight loss and injury in the right thoracic limb, already having histopathological diagnosis of squamous differentiation adenocarcinoma through biopsy. Physical examination showed no other clinical signs at first, including no signs of respiratory disease. Laboratory and imaging exams were performed, and the radiographic examination showed alterations in the pulmonary parenchyma showing a nodular area of increased radiographic density. Followed up by the manifestation of breathing noise at rest, as the first respiratory signs. The association of the clinical evaluation, medical history, and histopathological report from the limb lesion, lead to the suspicion diagnostic of lung-digit syndrome. The owners decide for the palliative treatment with chemotherapy, using carboplatin and prednisolone. Only the first session was performed, with the animal being euthanized due to clinical worsening 48 days after the initial manifestation of clinical signs. The diagnosis was confirmed by post mortem exams, and the pulmonary nodule were diagnosed as adenocarcinoma with squamous differentiation in concordance with the limb lesion diagnosis. Discussion: The lung-digit syndrome is still poorly studied in the veterinary medicine, with few reports published. Epidemiological data shows major incidence in elderly cats, with no racial or sexual predisposition, occurring in a 12-year-old cat in the present case. There are few theorys to explain the etiopathogenesis of the syndrome, however, none have been fully comproved. The clinical symptomatology varies from asymptomatic animals to those manifesting nonspecific systemic signs and respiratory signs. In this case the animal initially manifested only the presence of the digit injury and weight loss, with respiratory signs manifesting later. The digital lesion local signs usually include swelling, ulceration, purulent discharge, nail loss, and pain, occurring more frequently in the thoracic limbs, involving weight-bearing digits, as in the present report that occurred in the right thoracic limb, with involvement of the first and third digits. Radiographic findings may help in the diagnosis suspicion, having the confirmation by histopathological examination. The most frequent histological types involved in the syndrome are the adenocarcinoma, bronchoalveolar carcinoma, squamous cell carcinoma and adenosquamous carcinoma. The squamous-differentiated adenocarcinoma or adenosquamous carcinoma, as described in the histopathological report in the present case, is the least frequent. The treatment protocol is not well-established with no proven effective treatment. Surgical excision is not recomended as a palliative method, and the chemotherapy and radiotherapy sucess rates are still unknown. The prognosis is considered extremely unfavorable and early diagnosis represents the best attempt to control the disease.